O silenciamento de Madalena na dialética hegeliana do Senhor-Escravo, em São Bernardo: uma perspectiva da Linguística Sistêmico-Funcional - Pastore, Fabiana (2019)
The purpose of this doctoral dissertation is the examination of the relationship of the central couple: Madalena and Paulo Honório, in the masterpiece of Graciliano Ramos, São Bernardo, focusing on the issue of the silencing of the wife, in the face of the aggressiveness of the husband. From the representational point of view, the husband sees the wife as his property, which, in terms of the Hegelian dialectic of the master-slave, attributes to Paulo Honório the role of master and to Madalena the role of slave. This philosophical-ideological concept is demonstrated in this research, with the support of evaluative semantics, within the Systemic-Functional Linguistics (SLF), known as appraisal. In addition, readers are sensitive to syndromes or complexes of evaluative meaning and to the ways in which they confirm, oppose or transform word choices elsewhere in the text, a process that involves also the notion of meta-relationship. Concomitantly, the metaphor here beside the metonymy supports the examination Madalena’s silencing within the Hegelian dialectic. Therefore, SFL is a theoretical-methodological proposal that makes it possible to verify the relationship between the microstructure of the lexical-grammatical choices of the text and the macrostructure of the power relations and the ideology of discourse and will be the methodology adopted in the analyses. The research must answer the following questions: (a) How can the lexicographical choices of the author identify the master versus slave relationship in the Paulo Honório and Madalena relationship? (b) What is the role of appraisal and metaphor in this process? (c) What is the relationship between Madalena’ silencing, the metonymy and ideological criticism involved in the novel? The results of the analysis showed that Madalena’ silencing is gradual and is related to the sense of inferiority of Paulo Honório, which perceives the intellectual superiority of his wife and resorts to violence as a way of reestablishing his power of lord/owner in the relationship, thus, a struggle for the recognition and establishment of roles in the resolutions of the narrative could be observed